2014
DOI: 10.1016/j.neuroscience.2014.07.063
|View full text |Cite
|
Sign up to set email alerts
|

Microbats appear to have adult hippocampal neurogenesis, but post-capture stress causes a rapid decline in the number of neurons expressing doublecortin

Abstract: Highlights• Clear adult neurogenesis was observed in three species of microchiropterans.• Microchiropteran adult neurogenesis is similar to that of other mammals.• Capture stress causes a rapid decline in detectable hippocampal neurogenesis.• Adult hippocampal neurogenesis appears to be a common mammalian neural trait. Abstract:A previous study looking for evidence of adult hippocampal neurogenesis in microchiropteran bats failed to reveal the strong presence of this neural trait. As microchiropterans have a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 42 publications
2
21
0
2
Order By: Relevance
“…2F). The absence of AHN was confirmed in the wild North American brown bat (Eptesicus fuscus ]), but not in a series of other African bats (Chawana et al 2014), in which the expression of DCX immunoreactivity depended on the duration of posttrapping handling stress. Interestingly, our laboratory-bred tropical bats that were adapted to human handling and perfused within minutes after catching were also AHN negative using multiple AHN markers (Amrein et al 2007).…”
Section: Evidence Of Hippocampal Neurogenesis In Other Wild and Domesmentioning
confidence: 84%
“…2F). The absence of AHN was confirmed in the wild North American brown bat (Eptesicus fuscus ]), but not in a series of other African bats (Chawana et al 2014), in which the expression of DCX immunoreactivity depended on the duration of posttrapping handling stress. Interestingly, our laboratory-bred tropical bats that were adapted to human handling and perfused within minutes after catching were also AHN negative using multiple AHN markers (Amrein et al 2007).…”
Section: Evidence Of Hippocampal Neurogenesis In Other Wild and Domesmentioning
confidence: 84%
“…While not parcellated into distinct regions, the dentate gyrus is one of the few regions of the adult brain to maintain neurogenesis throughout much of the adult life of mammals (Kempermann, 2012). Adult hippocampal neurogenesis has been reported in the dentate gyrus of all mammalian species studied to date (Cavegn et al, 2013;Chawana et al, 2014;Fasemore et al, 2018;Kempermann, 2012;Patzke et al, , 2015 to the exception of cetaceans, where this neural trait appears to be absent (Patzke et al, 2015). The six-layered subicular complex is composed of four parts, the dorsal and ventral subiculum, presubiculum, parasubiculum, and subicular transitional cortex, while the six-layered entorhinal cortex is most often described as being composed of medial and lateral cortical areas, but detailed analyses indicate the presence of several more cortical areas in this region Paxinos & Watson, 2009;Schulz & Engelhardt, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, adult-born neurons are detected in the hypothalamus of several mammals including sheep, mouse, rats, vole, and hamster (Fowler et al, 2005; Xu et al, 2005; Pierce and Xu, 2010; Migaud et al, 2011; Mohr and Sisk, 2013; Robins et al, 2013; Batailler et al, 2014), suggesting that hypothalamic neurogenesis is a conserved process in mammals. Meanwhile, microchiropterans were previously reported to undergo no adult hippocampal neurogenesis (Amrein et al, 2007), later studies reported otherwise with significant expression of DCX detected via immunohistochemistry (Chawana et al, 2014). …”
Section: Introductionmentioning
confidence: 99%